Third Year University Students' Accounts for Choosing Chemistry. Issue 2 (4th May 2019) - Dagogo, Ibiye Tonye; Davidowitz, Bette; Taylor, Dale L.
Abstract : This study examined final year undergraduate chemistry students' choice of study programme offered at a large research-intensive university in South Africa, applying Social Cognitive Career Theory as a theoretical framework. The sample consisted of 18 students of diverse ethnicity and gender from both the extended curriculum programme and the mainstream programme who had successfully entered their final year chemistry course. These students were interviewed, and the transcripts were subjected to qualitative inductive thematic analysis. The study revealed that chemistry was a second-choice option for most of the students. Retrospective criteria significantly influenced the choice for the majority of extended curriculum programme students, especially those who chose chemistry as a second option. For the majority of the mainstream students who chose chemistry as either first or second option, it was a mixture of retrospective and prospective criteria, with a bias towards the prospective criteria. For this study, the university's requirement of a second major for the Bachelor of Science degree was an emerging reason for students choosing chemistry.